An analysis of the unified theory of acceptance and use of technology (UTAUT) to the adoption of electronic medical records in hospital settings - Ghozali, Muhammad Thesa; Rassyifa, Aloina Jean; Faradiba, Faradiba; Damanik, Ferina Septiani; Sari, Seftika; Satibi, Satibi; Fortwengel, Gerhard (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Electronic Medical Records (EMRs) are increasingly recognized as vital tools for enhancing the efficiency, accuracy, and quality of healthcare delivery. Despite regulatory mandates in Indonesia, the adoption of EMRs remains uneven, particularly in rural healthcare settings. This study applied the Unified Theory of Acceptance and apply of Technology (UTAUT) to investigate the behavioral intention of healthcare professionals working in private hospitals to use electronic medical records. A quantitative, cross-sectional design was implemented involving 90 participants selected through purposive sampling in an Indonesian hospital. The study's data were gathered between October 2024 and January 2025 using a validated 18-item UTAUT-based questionnaire. Data analysis was conducted with SPSS and SmartPLS software. Results indicated that all four UTAUT construct – Performance Expectancy (β = 0.200, p = 0.016), Effort Expectancy (β = 0.353, p < 0.001), Social Influence (β = 0.291, p < 0.001), and Facilitating Conditions (β = 0.262, p = 0.008 – had statistically significant positive effects on Behavioral Intention. The model demonstrated moderate explanatory power (R² = 0.655) and strong predictive relevance (Q² = 0.512). These results validate the UTAUT model's suitability in this context and provide practical insights for strengthening EMR implementation strategies. Future research should consider longitudinal approaches and multi-site comparisons to enhance generalizability and policy relevance.